Metacognitive strategies in teaching essay writing: Repeated measures in the creative writing classroom - Ramadhanti, Dina; Yanda, Diyan Permata (Politeknik Negeri Bali, 2025)
Metacognitive strategies are language learning strategies used to improve self-monitoring and self-regulation skills. Using a purposive sampling technique, 79 students in a creative writing class were selected to participate. Data collection was carried out repeatedly, and the data were analyzed using repeated measurement tests. During essay writing learning, students were guided to develop metacognitive skills, starting from planning, monitoring, and evaluating writing. The results of the study showed that metacognitive strategies influenced the development of metacognitive skills. Students were accustomed to writing in the stages of planning writing, monitoring the strategies used, and evaluating the writing results. When completing their writing, they were guided to use a reflection journal as a self-reflection tool. Measurements were carried out five times. In the first week, students began to be introduced to metacognitive strategies with a focus on awareness of the thinking process, especially in planning the content of the writing; in the second week, students showed significant improvement when they were able to organize ideas more coherently and relevantly to the topic; In week 3, students demonstrated maturity in developing arguments, enriching descriptions, and improving paragraph cohesion and coherence, resulting in a significant increase in their creative essay writing scores. However, in weeks 4 and 5, students' abilities slowed down, with no statistically significant differences. This stagnation was caused by the learning plateau and ceiling effect, the short duration of treatment, inaccurate assessment instruments, and student motivation and boredom. Nevertheless, metacognitive strategies are recommended for use in essay writing learning.